A Decentralised Approach to Wastewater Management in the Urbanising Region: The Case of Jakarta, Indonesia. (November 2017) - Putri, Prathiwi Widyatmi
State-led and market-oriented approaches to sanitation development in Jakarta have favoured the construction of large-scale centralised sewerage systems. This development approach is not always suitable because the principles of modern infrastructure underlying the technological systems are not applicable in informal settlements scattered over the metropolis. Due to spatial fragmentation within the built environment, diverse socio-economic and fragile geo-ecological conditions in different settlements and the city as a whole, Jakarta needs to adopt a decentralised approach to wastewater management. This article examines governmental dynamics in Jakarta and analyses a sanitation project to introduce improved septic tanks and community sludge-hauling enterprises. The presence of (international) NGOs and civil society organisations is often vital to help communities enrich their technical knowledge of environmental problems and expand their sociopolitical networks. Nevertheless, local initiatives provide a limited response to community sanitation needs and sanitation problems beyond the neighbourhood level. This article argues that the introduction of decentralised sanitation systems requires a new form of state-led infrastructure provision, which involves the (transformative) participation of local actors. In doing so, it extends the notion of decentralised wastewater management beyond purely technological concerns.